2019
DOI: 10.1080/15384101.2019.1669998
|View full text |Cite|
|
Sign up to set email alerts
|

Astragalus root extract inhibits retinal cell apoptosis and repairs damaged retinal neovascularization in retinopathy of prematurity

Abstract: Since the functions of Astragalus root extract in retinopathy remain to be unraveled, this study is performed to elucidate whether Astragalus root extract functions in retinal cell apoptosis and angiogenesis in retinopathy of prematurity (ROP). Newborn mice were selected for establishing mice models of oxygen-induced retinopathy (OIR), which were treated with high-, medium-or low-Astragalus root extract. Evans Blue (EB) was perfused to detect the blood retinal barrier. Additionally, the vascular morphology, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Wang et al reported that the main functions of osteoblasts which induced from stem cells were to synthesize bone matrix and promote mineralization of the matrix to form bone tissue [30]. The excellent osteoblast proliferation ability could accelerate the occurrence of osteointegration on the surface of the materials [31]. Yuan et al reported that osteoblast apoptosis was related to bone reconstruction in multiple parts of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that the main functions of osteoblasts which induced from stem cells were to synthesize bone matrix and promote mineralization of the matrix to form bone tissue [30]. The excellent osteoblast proliferation ability could accelerate the occurrence of osteointegration on the surface of the materials [31]. Yuan et al reported that osteoblast apoptosis was related to bone reconstruction in multiple parts of the body.…”
Section: Discussionmentioning
confidence: 99%
“…They act as anti-angiogenic agents to directly inhibit VEGF production and reduce avascular and neovascular areas after treatments. Other plant extracts including Aster koraiensis extract, Astragalus root extract, and Cnidium officinale extract also exert beneficial effects after OIR, resulting in vascular protection and the inhibition of angiogenic agents release [ 76 , 77 , 78 ]. It is important to remember that these are plant extracts but not a pure compound and thus contain other compounds that are present inside the plant.…”
Section: Nutritional Supplementsmentioning
confidence: 99%